2014
DOI: 10.4097/kjae.2014.66.1.18
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical duration and recovery characteristics of cisatracurium after priming using rocuronium or cisatracurium: preliminary study

Abstract: BackgroundThe priming technique can speed up the onset of cisatracurium during intubation. However, there have been no reports on the effect of the priming technique on duration or recovery profile of cisatracurium. Therefore, we attempted to determine whether or not a priming technique with rocuronium or cisatracurium can affect clinical duration or recovery profiles of cisatracurium.MethodsA total of 36 patients, ASA I and II, who were scheduled to undergo elective surgery, were enrolled. The patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Cisatracurium was widely used in Badaoui's study (6), in contrast to this study. Several studies have shown that there is no difference in muscle relaxation between rocuronium and cisatracurium (35) This study has the weakness of being monocentric, but confirms the high frequency of complications in bariatric surgery.…”
Section: Variablessupporting
confidence: 79%
“…Cisatracurium was widely used in Badaoui's study (6), in contrast to this study. Several studies have shown that there is no difference in muscle relaxation between rocuronium and cisatracurium (35) This study has the weakness of being monocentric, but confirms the high frequency of complications in bariatric surgery.…”
Section: Variablessupporting
confidence: 79%
“…As early as the 1990s, there was evidence that rocuronium can produce a more rapid onset of muscle relaxation than cisatracurium with equipotent intubating doses [ 22 ]. Other studies also showed that rocuronium provides shorter onset time [ 23 26 ], and priming with rocuronium significantly accelerated onset of cisatracurium [ 27 ]. Previous studies have also compared cisatracurium with rocuronium in tracheal intubation condition.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Uso simultâneo de BNMs adespolarizantes O uso simultâneo de BNMs adespolarizantes da mesma classe tende a promover interação aditiva, enquanto BNMs de diferentes classes interagem de forma sinérgica por afinidades distintas aos receptores pré e pós-sinápticos de acetilcolina. 21,[23][24][25] A duração do efeito clínico resultante do uso de BNMs diferentes depende da sequência de administração, pois a maioria dos receptores de acetilcolina permanece ligada à primeira droga injetada, predominando suas características no bloqueio. 24 Doses priming utilizadas para acelerar o início de ação dos BNMs são tão baixas que a interação sinérgica ou aditiva entre as drogas parece tornar-se pouco significativa.…”
Section: Bnms Adespolarizantes E Succinilcolinaunclassified
“…24 Doses priming utilizadas para acelerar o início de ação dos BNMs são tão baixas que a interação sinérgica ou aditiva entre as drogas parece tornar-se pouco significativa. 25…”
Section: Bnms Adespolarizantes E Succinilcolinaunclassified